1997
DOI: 10.1002/(sici)1097-0215(19970410)71:2<267::aid-ijc23>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an anti-tumour immune response in a non-immunogenic tumour: HSVtk killing in vivo stimulates a mononuclear cell infiltrate and a Th1-like profile of intratumoural cytokine expression

Abstract: Direct delivery of the herpes simplex virus thymidine kinase (HSVtk) gene, in combination with the prodrug ganciclovir (GC), has been used for the treatment of localised, inoperable tumours. Several groups have shown that when rodent tumours are ablated in vivo with suicide genes, antitumour immunity can also be generated. Hence, this approach may also be useful in treating disseminated disease. Here we have studied the mechanisms associated with this anti-tumour immunity. In B16 HSVtk 1 tumours being killed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(56 citation statements)
references
References 14 publications
5
49
1
1
Order By: Relevance
“…The presence of an intense in¯ammatory in®ltrate has been described in the regressing tumours of immunocompetent animals treated with GDEPT systems (HSV TK/GCV, Caruso et al, 1993;Vile et al, 1997;Yamamoto et al, 1997;CD/5-FC, Consalvo et al, 1995;Kuriyama et al, 1999a). Moreover, it has been noticed that the bystander effect was signi®cantly reduced in immunode®cient athymic mice (Vile et al, 1994;Gagandeep et al, 1996;Pavlovic et al, 1996;Ramesh et al, 1996;Bi et al, 1997;Kuriyama et al, 1999a) and after sublethal irradiation (Ramesh et al, 1996).…”
Section: The Bystander Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of an intense in¯ammatory in®ltrate has been described in the regressing tumours of immunocompetent animals treated with GDEPT systems (HSV TK/GCV, Caruso et al, 1993;Vile et al, 1997;Yamamoto et al, 1997;CD/5-FC, Consalvo et al, 1995;Kuriyama et al, 1999a). Moreover, it has been noticed that the bystander effect was signi®cantly reduced in immunode®cient athymic mice (Vile et al, 1994;Gagandeep et al, 1996;Pavlovic et al, 1996;Ramesh et al, 1996;Bi et al, 1997;Kuriyama et al, 1999a) and after sublethal irradiation (Ramesh et al, 1996).…”
Section: The Bystander Effectmentioning
confidence: 99%
“…Cotransfection of cytokine-and suicide genebased vectors followed by prodrug treatment has met with varying results (Chen et al, 1995;Castleden et al, 1997;Coll et al, 1997;Moriuchi et al, 1998;Nanni et al, 1998;Pizzato et al, 1998;Cao et al, 2000). Combined adenoviral delivery of CD/5-FC and murine interleukin-2 (IL-2) to mice inoculated with erythroleukemia cells induced more potent tumour growth inhibition and longer survival than the separate treatments (Ju et al, 1998).…”
Section: The Bystander Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…T-cells, and CD8 ? T-cells, and elicits an anti-tumor inflammatory response [26]. However, the GCV clinical trial results revealed that delivery of HSV.tk alone by adenoviral vehicles into tumors did not achieve the required antitumor efficacy due to limited infection and lack of potency.…”
Section: Discussionmentioning
confidence: 99%